The Contribution of Multi-Cultural and Interreligious Education in Spiritual, Moral and Cultural Development of Students (Придонес на мултикултурното и меѓурелигиското образование во духовниот, моралниот и културниот развој кај учениците) - Aneta Jovkovska (Univerzitet „Sv. Kiril i Metodij“, Filozofski fakultet, Institut za Pedagogija, Skopje, 2016)
Cultural globalization and socio-cultural changes taking place in modern society, as well as the integration and differentiation of national cultures, have a significant influence on the actualization of the problem of multicultural education of younger generations. On the other hand, one of the key educational goals in primary, secondary and higher education is the development of the students’ personality, their spiritual and moral culture, which is primarily expressed in the system of moral, spiritual, and civic values, and the ability to lead their lives in a fertile interaction with representatives of other cultures in addition to the necessity of maintaining, enhancing and extending cultural values of their own nation and simultaneously adhering to the values of other nations. Hence, inter-ethnic and inter-religious tolerance among students is an active moral position of the person, which can be expressed in readiness to recognize, accept, understand, and respect the ethnic and religious diversity and originality in the process of interaction of subjects and in conditions of a multi-ethnic society. Investigation of the problem of establishing inter-ethnic and inter-religious tolerance among students in the educational system stems from both the socio-cultural situation in Macedonia and the wider global community. This paper relayed the views of leading world scientists who study this phenomenon. Furthermore, it also explored and presented the differences between primary school students from Macedonian and Albanian ethnicity in terms of their expressed respect for different cultures and religions and their developed skills of tolerance, dialogue, respect, and cooperation with students from other ethnic and religious affiliation.
Internacional Journal for Education Research and Training (IJERT) Volume 2, Issue 1, 2016
Keywords: Inter-cultural education, tolerance, respect, values, dialogue, cooperation